CD4/CD8 ratio normalisation and non-AIDS-related events in individuals with HIV who achieve viral load suppression with antiretroviral therapy: an observational cohort study. Issue 3 (March 2015) - Mussini, Cristina; Lorenzini, Patrizia; Cozzi-Lepri, Alessandro; Lapadula, Giuseppe; Marchetti, Giulia; Nicastri, Emanuele; Cingolani, Antonella; Lichtner, Miriam; Antinori, Andrea; Gori, Andrea; Monforte, Antonella d'Arminio
Summary: Background: In patients with HIV, immune reconstitution after antiretroviral therapy (ART) is often incomplete. We assessed the probability of patients reaching a CD4/CD8 ratio of 1 or more after the start of ART and its association with the onset of non-AIDS-defining events and death. Methods: We did an analysis of the ICONA cohort, which recruited treatment-naive patients with HIV in Italy. We included participants in the cohort who started ART, reached an undetectable viral load (≤80 copies per mL), and had a CD4/CD8 ratio of less than 0·8 at the time of an undetectable viral load. We defined ratio normalisation in patients as two consecutive values of 1 or more. We used Kaplan-Meier curves to estimate the cumulative probability of ratio normalisation. We then used Poisson regression models to identify factors independently associated with normalisation and with progression to non-AIDS-defining events or death. Findings: We included 3236 participants, enrolled between Jan 22, 1997, and Feb 25, 2013. At the start of ART, median CD4/CD8 ratio in our population was 0·39 (IQR 0·26–0·55). 458 (14%) patients reached a CD4/CD8 ratio of 1 or more; the estimated probability of normalisation was 4·4% (95% CI 3·7–5·2) by 1 year from baseline, 11·5% (10·2–13·0) by 2 years, and 29·4% (26·7–32·4) by 5 years. Factors associated with normalisation were high pre-ART CD4 cell counts, a high CD4/CD8 ratio at baseline, and negative cytomegalovirus serological findings. The incidence rate of non-AIDS-defining events for patients with a CD4/CD8 ratio of less than 0·30 (4·2 per 100 patient-years, 95% CI 3·4–5·3) was double that for those with a ratio of 0·30–0·45 (2·3, 2·1–2·5) or more than 0·45 (2·2, 1·7–2·9). A ratio of less than 0·30 was independently associated with an increased risk of non-AIDS-defining events or death compared with one of more than 0·45. Interpretation: Few patients had normalised CD4/CD8 ratios, even though they had viral suppression. Low ratios were associated with increased risk of serious events and deaths. The CD4/CD8 ratio could be used by clinicians to identity patients at risk of non-AIDS-related events. Funding: AbbVie, Bristol-Myers Squibb, Gilead, Janssen, Merck Sharp & Dohme, ViiV Italy.